Evaluation of rheological parameters of the axial system using the Transfer Vibration through Spine (TVS) method - Panska, Sarka; Piglova, Tereza; Zeman, Josef; Marsik, Frantisek; Lopot, Frantisek; Jelen, Karel (Neuro-endocrinology letters, 2016)
OBJECTIVE: The human motion system reacts to both hypo and hyperactivity loads by changes to the rheological properties of tissues. This study deals with changes to the axial system (AS) compartment. Using the appropriate methodologies and mathematical-physical methods, these changes can be identified and quantified. METHODS: This study describes the noninvasive TVS (Transfer Vibration through Spine) method, which was applied to assess the AS selected mechanical properties in various modes. A pilot study was conducted on a top-level twelve-year-old girl-gymnast. The data detection was carried out in three cycles, before and after a peak 3.5 hour training session and the next day, after resting, just before the next training. RESULTS: Specifically, the values of selected rheological parameters, the AS damping coefficient b and viscosity μ, were obtained. The dynamics of their changes, in the stated load cycles, has also been shown. The damping coefficient b fell from the value of 0.626 to 0.324 before training and increased to 0.394 after resting. The viscosity coefficient μ showed a similar trend, namely falling from the value of 9.85 [Pa.s] to 2.15 [Pa.s] and then increasing to 3.8 [Pa.s] . CONCLUSIONS: With its computational solution, the TVS method,is a diagnostic apparatus making it possible to classify AS properties, both quantitatively and qualitatively, or its chosen segments and their changes, respectively. It can be used in classifying, preventing and treating the consequences of extreme motion and relaxing modes. The TVS application also makes it possible to control AS states over therapeutic, recovery, ergonomic and other loading modes of the human locomotion system.
Keywords: viskozita; biomechanika; Child; Viscosity; Humans; vibrace; lidé; Vibration; reologie; gymnastika; zatížení muskuloskeletálního systému; Pilot Projects; Female; pilotní projekty; Rheology; ženské pohlaví; Spine; Biomechanical Phenomena; Gymnastics; dítě; Weight-Bearing; páteř